Chemical composition and biological activities of whole and dehulled hemp (Cannabis sativa L.) seeds - Alonso-Esteban, José Ignacio (2018)
This study aimed to determine a complete chemical composition of eight different varieties of whole hemp seeds and eight samples of commercial dehulled hemp seeds. We also evaluated the phenolic profiles and antioxidant, cytotoxic, and antimicrobial properties of hydromethanolic seed extracts. Whole hemp seeds contain much more fibre than dehulled hemp seeds, which contain more fat and protein. Sucrose and raffinose were the most abundant soluble sugars, and citric and oxalic acids were the most abundant organic acids. In the hydromethanolic hemp seed extracts, we detected the phenolic acids ferulic acid-hexoside and syringic acid. Whole hemp seed extracts exhibited better antioxidant activity than dehulled hemp seed extracts, especially in the TBARS assay. Cytotoxic activity against NCI-H460 cells was also observed. The dehulled hemp seed extracts displayed antibacterial activity, especially against Bacillus cereus, Listeria monocytogenes, and Enterococcus faecalis, and antifungal activity to a lesser extent.